Codesign Challenges for Exascale Systems: Performance, Power, and Reliability. - Kerbyson, Darren; Vishnu, Abhinav; Barker, Kevin; Hoisie, Adolfy (Computer (00189162), 2011)
The complexity of large-scale parallel systems necessitates the simultaneous optimization of multiple hardware and software components to meet performance, efficiency, and fault-tolerance goals. A codesign methodology using modeling can benefit systems on the path to exascale computing.